La escasez de alimentos en la Guerra de Cuba - Sarmiento Ramírez, Ismael; Mosquera, Martha (Militaria. Revista de cultura militar, 2004)
This essay proves that very few branches of the Cuban Liberating Army where well fed and supplied during the wars against Spain (1868-1898). The soldiers could shift from abundance to the lack of the most elementary sources of nourishment. The lack of food was one of the disadvantages that the Cuban rebels had to cope with constantly. This forced them to try and find a variety of nutritional formulae.
Keywords: Cuba; Independence Wars; Liberating Army; Nourishment; Shortage